ANALISIS KEMAMPUAN NUMERASI DITINJAU DARI KEBIASAAN BERPIKIR KRITIS DAN MATEMATIKA PADA PRESTASI SISWA - Bella Dharera, Nyeli; Purwosetiyono, FX Didik; Dwi Setyawati, Rina (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2025)
The purpose of this article is to examine students' numeracy skills through critical and mathematical thinking habits, as well as find out the impact on students' learning achievement. And to get a better understanding of how students' numeracy skills, critical thinking habits and mathematical abilities correlate with each other. Based on the results of the literature review of journals, books and scientific articles analyzed, it was found that one of the important elements in mathematics education is numeracy, which requires critical and mathematical thinking skills to solve problems effectively. The results of this research will later show that students who have strong critical and mathematical thinking habits tend to have better numeracy skills and better academic achievement and provide implications for teachers and educators to design learning strategies that integrate the development of critical thinking. Apart from that, learning that emphasizes critical thinking habits also shows good results.